A comparative study of emotional intelligence in addiction to opium and non-addicted men (Drug Control Headquarters, Research and Education Office, 2009)
Preface:The aim of this study was to comparison between Emotional intelligence and its chip scales in addicted and non-addicted men. Method:Method of study was Sausal-Comparative. Sample include the One hundred and twenty (60 addiction to opium and 60 non-addicted). The addicted group sample was selected from among clients of Eskandari addiction treatment clinic and the non-addicted group was selected from among scholars and staff of state university settling in Tehran . sample groups were selected by Available Sampling Method. In order to assess the emotional intelligence and its chip scales for each subject, the Bar-On Emotional intelligence Test(version 90 question) was administered. For input analysis statistical soft-ware(SPSS) was aplyed and "t" independent-statistical test was applied to compare two groups. Finding:The results illustrat that addicted men have a meaningful difference in Emotional intelligence and chip scales of Problem Solving, self-Actualization, Emotional self-Awarness, self-Regard, Responsibility, Stress Tolerance, Reality Testing, Impulse Control, Flexability, Assertivencess, Happiness and Optimism, comparing with non-addicted men, but there is no meaningful difference between two groups, average in chip scale of Interpersonal Relationship .